CORRELATION INTERRELATION OF PSYCHOEMOTIONAL STATE OF CHILDRENWITH SOCIO-HYGIENIC FACTORS OF CARIES OCCURRENCE - L.F. Kaskova; K.M. Popyk; L.P. Ulasevych; L.D. Korovina (Ukrainian Medical Stomatological Academy, 2019)
Questionnaire is one of the possible ways of research in organized children's groups, which allows us to identify socio-hygienic factors of caries occurrence. Proper oral hygiene, awareness of children about this, regular preventive visits to a dentist, knowledge about the possibility of caries prevention play an important role in caries prevention. Lately, a great attention is paid to the psycho-emotional state of adult patients and especially of children due to the impact school strain and the formation of behavioral responses on them. The aim of our research was to study the correlation interrelation between the psycho-emotional state of children from 6 to 16-year-old with the socio-hygienic factors of dental caries occurrence. Dental survey, analysis of the emotional state and interrogation of children and their parents were performed in 295 children from 6 to 16-year-old. Children and their parents were interviewed in order to study the influence of socio-hygienic factors on the possibility of caries occurence. Psycho-emotional state was studied by the following methods:  method of definition of school fears, kinetic image of the family, Spielberg's self-esteem scale of personal anxiety level. Definition of school fears has revealed that 13.2% of the surveyed children had signs of general school fear, 15.6% had a fear of social contacts with peers, 10.2% had a fear of social contact with teachers, 17.0% had a fear of self-expression, 10.2% had a fear of knowledge test situations, 38.6% had a fear of not meeting the expectations of others, 14.6% had low physiological resistance to school fears. Anxiety (by Spielberg`s method) was found in 80.3% of surveyed. Only general school fear (rs = 0.17, p <0.005) correlated with the children age. Its frequency increases in 2.6 times after 12 years age. Only 36.1% of children did not experience psychological distress inside of their families. However, tensed relationship inside of families was not determined in 51.4% of children without caries and only in 22.1% of children with caries (pMU <0.001). There are correlation interelationships between caries development and tensed relationships inside of families and general school fear, less pronounced correlation between carious process activity and tension inside of families and general school fear. Children with low physiological resistance to school fears have the least complaints about the condition of tooth hard tissues. However, complaints do not have significant interrelation with caries presence. Children with caries do not have complaints about the presence of carious cavities in teeth, rarely complain on discoloration, misalignment or irregular shape teeth, equaly as children without caries. Children with a fear of knowledge testing are the most likely to complain about the presence of carious cavities. Children who can better resist to school fears are more likely to visit a dentist for a preventive purpose. Children who have a fear of social contact with teachers or fear of unsettled meeting the expectations of others are less likely to seek a preventative meeting with a dentist. Increasing anxiety (according to Spielberg`s method) contributes to preventive treatment. Low physiological resistance to school fears indicates the risk that, even if there is pain in a tooth, children do not seek for a dental support. During the questionnaire of children the dependence of general school fear presence with the age of the child was found, which frequency increases in 2.6 times after 12 years age. There is a correlation interrelationship between the frequency of attendance of a dentist and the presence of a common school fear, ie, greater the fear, less attendences of a dentist. Greater the children`s general school fear is observed, greater the anxiety during the dentist appointment is noted. The results are improved according to work with children and their parents on the regulation of the emotional state of children.